Faktor-Faktor Yang Berperan Pada Perilaku Sadari Wanita Usia Subur Di Tempat Praktek Mandiri Bidan Endang Sundari Bekasi Tahun 2022 - Sundari, Endang; Utami, Sri; Ariestanti, Yenni (Ikatan Bidan Indonesia (IBI), 2022)
The prevalence of cancer in West Java is still relatively high. In the city of Bekasi there was an increase in the presentation of breast cancer for women aged 30-50 years from 2017 by 77 people (1.85%) to 91 people (4.18%) in 2018. This is due to a lack of knowledge and awareness of doing BSE to prevent breast cancer. breast cancer. The purpose of the study was to analyze the factors that play a role in BSE behavior in WUS at the Endang Sundari Midwife's Independent Practice Center in Bekasi in 2022. This study used a cross sectional design, the number of samples was 123 respondents. The sample used using inclusion criteria, namely not pregnant or breastfeeding, can read and write and the exclusion criteria are having breast cancer experience. The questionnaire used has been tested for validity and reliability. Analysis using univariate, bivariate and multivariate using multiple logistic regression. The results showed that respondents with good BSE behavior were 62.6%. Bivariate analysis showed that education variables (p value = 0.000), knowledge (p value = 0.000), BSE attitudes (p value = 0.000), family support (p value = 0.008,) and BSE information exposure (p value = 0.000) were significantly related. with BSE behavior in women of childbearing age. While the variables of age and education are not significantly related. Multivariate analysis showed that the dominant variable was knowledge of OR of 17.7, meaning that WUS who had good knowledge of BSE will have a good chance of BSE behavior 17.7 times higher than those who have poor knowledge of BSE after being controlled by the education variable, support family and exposure to BSE information. Thus, knowledge accompanied by higher education and exposure to information is important to change BSE behavior.